Age of the World's Oldest Rocks Refined Using Canada's SHRIMP: The Acasta Gneiss Complex, Northwest Territories, Canada - Stern, Richard; Bleeker, Wouter (Geoscience Canada, 1998)
Summary The Sensitive High Resolution Ion Micro-probe (SHRIMP) at the Geological Survey of Canada, Ottawa, has been used to show that the oldest-known continental crust is even older than previously thought. Zircon grains from a deformed igneous rock from the Acasta Gneiss Complex, Northwest Territories, Canada, are interpreted, based on their U-Pb isotope systematics, to have crystallized at-4.03 Ga. Subsequent high-grade metamorphism at -3.36 Ga and later resulted in extensive Pb-loss and growth of metamorphic zircon. This is one of the few rocks known to have survived the first 500 million years of Earth's history.